KONSTRUKSI NILAI DALAM VISI ISLAM YANG BERKESEMESTAAN: SUATU TINJAUAN FILOSOFIS: IRWANDRA - -, IRWANDRA (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2022)
Such dimensions like sacred and profane, physical and spiritual; are the examples of how seriously does Islam pay attention to the problem of life as well as representing part of Islamic way of life. Universality and absoluteness in one hand, and relative-particular and keep-changing in the other hand, are some of principles set up by Islam. These two standpoints are grasping and verifying to each other, not the other way around, negating each other. In this context, the understanding of rahmatan lil ‘ālamīn in Islam compromises and boosts both dimensions in life particularly in order to stand for the changes and the various indentity and values in life. This essay in trying to discuss Islamic teachings and values with hermeneutics-philosopical perspectives. The encounter and converge between Islam, values and culture allow an “earthier” standpoint. Theoritically, these priciples can be applied as a standard for Islamic way in encountering and facing other sort of values and cultures. Practically, whatever the dynamics and changes taking place in life should be meant as an enrichment, augmentation, and enlargement the universality feature of Islam.